Examining the World Bank Group lending and natural resource abundance induced financial development in KART countries - Gokmenoglu, Korhan K.; Rustamov, Bezhan (Elsevier Sci Ltd, 2019)
This study investigates the roles of the World Bank lending and abundance of natural resources in fostering the financial development of Kazakhstan, Azerbaijan, Russia, and Turkmenistan during the period from 1992 to 2017. Empirical findings confirm co-integration between the variables being investigated. The results of the dynamic ordinary least squares test indicate that in the long-run the World Bank lending and an abundance of natural resources positively affects financial development. We also confirm that excessive borrowing from the World Bank and faulty management of loans and credits from the bank negatively affect financial development. Empirical findings show that institutional quality has an impact on how effectively natural resources are managed. We discuss the policy implications of our study in detail in the conclusion section.
Keywords: World bank lending; Natural resources; Financial development; Developing countries